1997
DOI: 10.1136/adc.77.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal technetium labelled white cell scan in the colitis of chronic granulomatous disease

Abstract: A child with colitis was treated for Crohn's disease, diagnosed on history, clinical and colonoscopic findings, radiolabelled white cell bowel scan, and colonic histology. After septicaemia caused by an unusual organism, further investigation lead to a diagnosis of chronic granulomatous disease (CGD). The granulomatous colitis of CGD is clinically, histologically, and on white cell scanning, indistinguishable from that in Crohn's disease and should be considered in atypical cases. Infection with unusual 'pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…10 However, they were not seen in all patients but when present the accumulations of macrophages appeared to be both much more prominent and prolific than those seen in Crohn's disease. This feature, together with their pigment content and the lack of neutrophils makes them quite distinct from those observed in Crohn's disease.…”
Section: Discussionmentioning
confidence: 78%
“…10 However, they were not seen in all patients but when present the accumulations of macrophages appeared to be both much more prominent and prolific than those seen in Crohn's disease. This feature, together with their pigment content and the lack of neutrophils makes them quite distinct from those observed in Crohn's disease.…”
Section: Discussionmentioning
confidence: 78%
“…62 Approximately 50% of patients, however, also develop a noninfectious chronic inflammatory bowel disease strikingly similar to Crohn's disease. [63][64][65][66][67][68][69][70][71][72][73] Although 1 study suggested more frequent gastrointestinal involvement in patients with X-linked disease, 73 another found equal rates in the X-linked and autosomal recessive groups. 74 The series to date suggest that the primary clinical manifestation of CGD enteritis is abdominal pain and that up to one-third of patients demonstrate bowel obstruction at some time.…”
Section: Chronic Granulomatous Diseasementioning
confidence: 99%
“…Patients may also present with pneumonia, lung abscesses, osteomyelitis and a granulomatous colitis which is clinically and histologically indistinguishable from Crohn's disease. 3 The association of colitis with CGD might be expected to increase the likelihood of neutrophilic dermatoses such as pyoderma gangrenosum, Sweet's syndrome (acute, febrile neutrophilic dermatosis) and bowel-associated pustular dermatosis. However we have found only one report of a neutrophilic dermatosis associated with CGD: 4 in that case infantile Sweet's syndrome was thought to be the presenting manifestation of CGD.…”
Section: Reportmentioning
confidence: 99%